Colds as predictors of the onset and severity of COPD exacerbations - Johnston NW; Olsson M; Edsbäcker S; Gerhardsson de Verdier M; Gustafson P; McCrae C; Coyle PV; McIvor RA (International Journal of COPD, 2017)
Neil W Johnston,1 Marita Olsson,2 Staffan Edsbäcker,3 Maria Gerhardsson de Verdier,4 Per Gustafson,5 Christopher McCrae,3 Peter V Coyle,6 R Andrew McIvor11Department of Medicine, Firestone Institute for Respiratory Health, McMaster University, Hamilton, ON, Canada; 2Early Clinical Development Biometrics, 3Respiratory, Inflammation & Autoimmunity Unit, Innovative Medicines & Early Development, 4Medical Evidence and Observational Research Centre, 5Respiratory, Inflammation & Autoimmunity Translational Medicine Unit, Early Clinical Development, Innovative Medicines & Early Development, AstraZeneca Research and Development, Gothenburg, Molndal, Sweden; 6Regional Virology Laboratory, Belfast HS C Trust, Belfast, UKRationale: Common colds are associated with acute respiratory symptom exacerbations in COPD patients.Objective: To determine exacerbation risk and severity in COPD patients with/without coincident self-reported colds.Methods: Global initiative for chronic Obstructive Lung Disease stage I–IV COPD patients electronically transmitted respiratory symptom diaries to research staff daily between December 2006 and April 2009. Respiratory symptom worsening prompted contact by a study nurse and patient assessment to determine if a cold was present or an exacerbation underway. A composite daily symptom score was derived for each subject from diarized symptom data. The exacerbation/cold/virus relation was examined using a Poisson regression model, the relation of colds to respiratory symptom severity using generalized estimating equation models.Results: Daily diary transmission compliance of >97% enabled detection of all possible exacerbations. Among 262 exacerbations meeting Anthonisen criteria, 218 (83%) had cold-like symptoms present at their inception, but respiratory viruses were detected in only 106 (40%). Within-subject exacerbation risk was 30 times (95% confidence interval [CI]: 20, 47; P<0.001) greater with colds present. Compared to cold- and virus-negative exacerbations (n=57), the mean increase in composite symptom score in those cold and virus positive (n=79) was 0.93 (95% CI: 0.61, 1.25; P<0.001), cold-positive and virus-negative exacerbations (n=100) 0.51 (95% CI: 0.21, 0.81; P<0.001), cold-negative and virus-positive exacerbations (n=26) 0.58 (95% CI: 0.23, 0.94; P<0.001).Conclusion: This study emphasizes the importance of colds in COPD exacerbation risk and severity, even in the absence of virus detection. COPD patients should act promptly when cold symptoms appear to facilitate early intervention for exacerbation prevention or management.Keywords: COPD exacerbations, respiratory infection, COPD epidemiology, respiratory viruses, common cold